A record-linkage study of the development of hepatocellular carcinoma in persons with hepatitis C infection in Scotland - McDonald, S A (Nature Publishing Group, 2008)
We investigated trends in first-time hospital admissions and deaths attributable to hepatocellular carcinoma (HCC) in a large population-based cohort of 22 073 individuals diagnosed with hepatitis C viral (HCV) infection through laboratory testing in Scotland in 1991–2006. We identified new cases of HCC through record-linkage to the national inpatient hospital discharge database and deaths registry. A total of 172 persons diagnosed with HCV were admitted to hospital or died with first-time mention of HCC. Hepatocellular carcinoma incidence increased between 1996 and 2006 (average annual change of 6.1, 95% confidence interval (CI): 0.9–11.6%, P=0.021). The adjusted relative risk of HCC was greater for males (hazard ratio=2.7, 95% CI: 1.7–4.2), for those aged 60 years or older (hazard ratio=2.7, 95% CI: 1.9–4.1) compared with 50–59 years, and for those with a previous alcohol-related hospital admission (hazard ratio=2.5, 95% CI: 1.7–3.7). The risk of individuals diagnosed with HCV developing HCC was greatly increased compared with the general Scottish population (standardised incidence ratio=127, 95% CI: 102–156). Owing to the advancing age of the Scottish HCV-diagnosed population, the annual number of HCC cases is projected to increase, with a consequent increasing burden on the public healthcare system.